Słodkie trucizny. (Gdańsk : [s.n.], 1946)
Afisz inf. o wykładzie Antoniny Baczyńskiej na temat działania narkotyków, który miał miejsce 15.11.1946 r.
Keywords: Narkotyki -- zwalczanie -- Polska -- 1945-1970.; Gdańsk (Polska) -- 1945-1970 -- druki ulotne